Solvent Isotope Effect on Hydrogen-Transfer Reduction of CO2 into Formate with Glycerine by Alkaline Hydrothermal Reaction - Shen, Zheng; Gu, Minyan; Yang, Long; Liu, Shiyang; Zhang, Wei; Dong, Wenjie (Journal of Technology Innovations in Renewable Energy, 2015)
To examine the solvent isotope effect on hydrogen-transfer reduction of CO2 into formate with glycerine by alkaline hydrothermal reaction, intermediates were identified by 13C-NMR, 1H-NMR, 2H-NMR, LC-MS analyses. The results showed that (1) CO2 was indeed converted into abiogenic formate; (2) a ketone carbonyl group as intermediate product was formed on hydrogen-transfer reduction of CO2 into formate with glycerine by alkaline hydrothermal reaction; (3) acetol was the most probable intermediate in the first reaction by undergoing a dehydration rather than a dehydrogenation.